Rubber composite material for high-performance tire and preparation method of rubber composite material
By using specific raw material formulas and process treatments in tire rubber materials, the interface effect between silica and rubber is improved, and the problems of poor friction reduction effect, insufficient wear resistance and tear resistance of existing tire rubber materials under high load and high temperature conditions are solved, achieving high-performance wear resistance and tear resistance.
Patent Information
- Application Number
- CN202510302304.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-14
AI Technical Summary
The existing rubber materials for tires show poor friction reduction effects, insufficient wear resistance and tear resistance under high load and high temperature conditions, resulting in safety hazards.
A high-performance rubber composite material for tires is used, and its raw materials include nitrile rubber, styrene butadiene rubber, silicate mineral powder, nanosilica, etc. Through specific process treatment and formulation, the interface effect between silica and rubber is improved, and the good dispersion and cross-linking of nanosilica is promoted.
On the basis of satisfying the properties of rubber for tires, this composite material significantly improves wear resistance and tear resistance, reduces safety hazards, and exhibits excellent fixed-extension stress under low deformation conditions.
Smart Images

Figure CN119798803A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of rubber for tires, and in particular to a high-performance rubber composite material for tires and a preparation method thereof. Background Art
[0002] Today, the rubber industry is one of the important basic industries of the national economy. It not only provides people with daily necessities, medical and other light industrial rubber products that are indispensable in daily life, but also provides various rubber production equipment or rubber parts for heavy industries such as transportation, construction, and machinery. Rubber is becoming more and more widely used.
[0003] As one of the most important components of a car, the tire's main function is to bear the load of the car, ensure the friction between the wheel and the road, and transmit the torque of traction and braking. In recent years, with the increase in the number of cars, the amount of tire rubber used has increased. Tire rubber materials often need to be used under complex and harsh conditions. When driving, they are subjected to various extrusions, friction, loads, and high and low temperature effects, and the performance requirements for tire rubber materials are becoming more and more stringent.
[0004] At present, silica is used to partially replace the conventional reinforcing agent carbon black in rubber materials for tires in an attempt to reduce rolling resistance. However, the affinity of silica to rubber is worse than that of carbon black, and the reinforcement effect is poor. Although the dispersibility of silica can be improved, its reinforcement effect can be enhanced and rolling resistance can be reduced, the friction reduction effect is poor. At the same time, the wear resistance, tear resistance and other properties cannot meet the requirements, which can easily cause serious safety hazards. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a high-performance tire rubber composite material and a preparation method thereof.
[0006] A high-performance tire rubber composite material, the raw materials of which include, by mass, 50-100 parts of nitrile rubber, 10-30 parts of styrene-butadiene rubber, 10-20 parts of silicate mineral powder, 1-2 parts of saturated ammonia water, 5-10 parts of tetraethyl orthosilicate, 5-10 parts of amino-terminated liquid nitrile rubber, 1-5 parts of graphene oxide, 1-2 parts of carboxyl-terminated polyamidoamine, 5-10 parts of loaded silicon dioxide, 1-5 parts of organic bentonite, 0.1-1 parts of zinc oxide, 1-3 parts of a crosslinking agent, 1-2 parts of a vulcanization accelerator, 1-3 parts of an antioxidant, 1-3 parts of stearic acid, and 1-3 parts of a dispersant.
[0007] Preferably, the silicate mineral powder is at least one of talc powder, muscovite powder and montmorillonite powder.
[0008] Preferably, the cross-linking agent comprises sulfur and organic peroxide, and the mass ratio of sulfur to organic peroxide is 2-3:0.5-1.5.
[0009] Preferably, the organic peroxide is diisopropylbenzene peroxide or / and bis(tert-butylperoxyisopropyl)benzene.
[0010] Preferably, the vulcanization accelerator is triallyl isocyanurate and / or N,N'-m-phenylene bismaleimide.
[0011] Preferably, the dispersant is sodium methylene dinaphthalene sulfonate or triethylene glycol diisooctanoate.
[0012] Preferably, the antioxidant is at least one of antioxidant BLE, antioxidant 445, antioxidant 4010, antioxidant DNP, and antioxidant TMQ.
[0013] Preferably, the loaded silica is prepared by the following specific operation: zirconium acetate and yttrium acetate are added to water and stirred evenly, urea is added thereto, stirred at 80-90°C for 5-10 hours, centrifuged, washed, vacuum dried, added to ethanol aqueous solution, saturated ammonia water is added thereto and stirred evenly, tetraethyl orthosilicate is added thereto under stirring, stirred at 40-50°C for 5-15 hours, centrifuged, washed, and vacuum dried.
[0014] More preferably, the mass ratio of zirconium acetate, yttrium acetate, saturated aqueous ammonia and tetraethyl orthosilicate is 1-2:1-2:1-3:1-3.
[0015] The method for preparing the above-mentioned high-performance tire rubber composite material comprises the following steps: S1. Add silicate mineral powder to ethanol aqueous solution and ultrasonically treat for 1-2h, add saturated ammonia water and ultrasonically treat for 1-2h, add ethyl orthosilicate and ultrasonically treat for 1-2h under stirring, let stand for 2-6h, filter, wash, vacuum dry, grind and sieve; add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamide amine, stir at 70-80°C for 1-2h to obtain pretreated silicate; S2, mixing the pretreated silicate, loaded silica, organic bentonite, zinc oxide, vulcanization accelerator, and antioxidant to obtain a mixture; S3, mixing the nitrile rubber, styrene butadiene rubber and the mixed material for 10-20 minutes at a mixing temperature of 70-90° C., adding a crosslinking agent thereto, and mixing at 160-180° C. for 1-2 hours to obtain a mixed material; S4. Cool the mixed material to 110-130°C, add stearic acid and dispersant in sequence, and plasticize for 10-30 minutes to form sheets.
[0016] Preferably, in S1, the frequency of ultrasonic treatment after the silicate mineral powder is added to the ethanol aqueous solution is 5-15 kHz, the frequency of ultrasonic treatment after adding saturated ammonia water is 5-10 kHz, and the frequency of ultrasonic treatment after adding tetraethyl orthosilicate is 5-10 kHz.
[0017] Beneficial effects: The present invention can improve the interface between silica and rubber, thereby promoting good dispersion of silica in rubber and achieving good reinforcement effect, so that the composite material not only has excellent wear resistance, but also excellent tear resistance and high hardness. When used in tire products, it can effectively reduce safety hazards.
[0018] The present invention loads nano silicon dioxide on layered silicate minerals, which not only prevents the nano silicon dioxide from falling off easily, but also has excellent dispersibility with amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamide amine, and has high mutual bonding strength. Compared with directly adding layered silicate minerals, the product has excellent tear resistance and excellent tensile stress at a relatively low deformation (100%).
[0019] The present invention utilizes zirconium acetate and yttrium acetate to form a composite doping, loads nano silicon dioxide on the surface, and composites with pretreated silicate. It has excellent reinforcement effect without adding carbon black, and at the same time ensures the dispersibility of silicon dioxide. Multiple cross-linking sites are formed between the molecular chain segments of nitrile rubber and styrene-butadiene rubber, giving the product excellent wear resistance and tear resistance, and has better durability than ordinary tires.
[0020] The present invention adopts a specific raw material formula and combines a specific process to prepare a wear-resistant and tear-resistant rubber composite material. On the basis of meeting the performance requirements of rubber for tires, the composite material has excellent mechanical properties and good friction reduction effects. At the same time, the preparation method is simple and suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The figure is a comparison chart of the tensile strength and 100% modulus of the composite materials obtained in Example 5 and Comparative Examples 1-3.
[0022] Figure 2 It is a comparison chart of the elongation at break and tear strength of the composite materials obtained in Example 5 and Comparative Examples 1-3.
[0023] Figure 3 This is a comparison chart of friction coefficient and wear rate in dry friction and wear test (load of 60N and sliding speed of 70mm / s) of the composite materials obtained in Example 5 and Comparative Examples 1-3.
[0024] Figure 4 This is a comparison chart of the friction coefficient and wear rate in the dry friction and wear test (load of 140N and sliding speed of 300mm / s) of the composite materials obtained in Example 5 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0025] The present invention will be further explained below in conjunction with specific embodiments.
[0026] Embodiment 1: A rubber composite material for high-performance tires, the raw materials of which include: 50g of nitrile rubber, 10g of styrene-butadiene rubber, 10g of talc, 1g of saturated ammonia water, 5g of tetraethyl orthosilicate, 5g of amino-terminated liquid nitrile rubber, 1g of graphene oxide, 1g of 3.0-generation carboxyl-terminated polyamide amine, 5g of loaded silica, 1g of organic bentonite, 0.1g of zinc oxide, 1g of cross-linking agent, 1g of triallyl isocyanurate, 1g of antioxidant BLE, 1g of stearic acid, and 1g of sodium methylene dinaphthalene sulfonate.
[0027] The cross-linking agent is composed of sulfur and bis(tert-butylperoxyisopropyl)benzene in a mass ratio of 4:1.
[0028] The loaded silica was prepared by the following specific operation: 1 g of zirconium acetate and 1 g of yttrium acetate were added to 20 g of deionized water and stirred evenly, 1 g of urea was added thereto, stirred at 80°C for 5 h, centrifuged, washed, and vacuum dried, added to 20 g of 40% by mass ethanol aqueous solution, 1 g of saturated ammonia water was added thereto and stirred evenly, 1 g of tetraethyl orthosilicate was added thereto under stirring, stirred at 40°C for 5 h, centrifuged, washed, and vacuum dried.
[0029] The method for preparing the above-mentioned high-performance tire rubber composite material comprises the following steps: S1. Add talcum powder to 50g of 40% ethanol aqueous solution and ultrasonically treat it for 1h at an ultrasonic frequency of 5kHz. Add saturated ammonia water and ultrasonically treat it for 1h at an ultrasonic frequency of 5kHz. Add tetraethyl orthosilicate and ultrasonically treat it for 1h under stirring at an ultrasonic frequency of 5kHz. Let it stand for 2h, filter, wash with deionized water, vacuum dry, and grind through a 100-mesh sieve; add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamide amine, stir at a temperature of 70°C for 1h at a stirring speed of 100r / min to obtain pretreated silicate; S2, mixing the pretreated silicate, loaded silica, organic bentonite, zinc oxide, triallyl isocyanurate, and antioxidant BLE, and stirring at a speed of 50 r / min for 10 min to obtain a mixture; S3, putting the nitrile rubber, styrene butadiene rubber and the mixed material into an internal mixer and mixing for 10 min, the mixing temperature is 70° C., the internal mixer speed is 50 r / min, adding a crosslinking agent thereto, mixing at a temperature of 160° C. for 1-2 h, to obtain a mixed material; S4. Cool the mixed material to 110°C, add stearic acid and sodium methylene dinaphthalene sulfonate in sequence, and plasticize for 10 minutes, then transfer to an open mill to produce sheets.
[0030] Example 2: A rubber composite material for high-performance tires, the raw materials of which include: 100g of nitrile rubber, 30g of styrene-butadiene rubber, 20g of talc, 2g of saturated ammonia water, 10g of tetraethyl orthosilicate, 10g of amino-terminated liquid nitrile rubber, 5g of graphene oxide, 2g of 3.0-generation carboxyl-terminated polyamidoamine, 10g of loaded silica, 5g of organic bentonite, 1g of zinc oxide, 3g of cross-linking agent, 2g of N,N'-m-phenylene bismaleimide, 3g of antioxidant 445, 3g of stearic acid, and 3g of sodium methylene dinaphthalene sulfonate.
[0031] The cross-linking agent is composed of sulfur and dicumyl peroxide in a mass ratio of 2:1.
[0032] The loaded silica was prepared by the following specific operation: 2 g of zirconium acetate and 2 g of yttrium acetate were added to 50 g of deionized water and stirred evenly, 5 g of urea was added thereto, stirred at 90°C for 10 h, centrifuged, washed, and vacuum dried, added to 50 g of 60% ethanol aqueous solution, 3 g of saturated ammonia water was added thereto and stirred evenly, 3 g of tetraethyl orthosilicate was added thereto under stirring, stirred at 50°C for 15 h, centrifuged, washed, and vacuum dried.
[0033] The method for preparing the above-mentioned high-performance tire rubber composite material comprises the following steps: S1. Add talcum powder to 100g of 60% ethanol aqueous solution and ultrasonically treat for 2h at an ultrasonic frequency of 15kHz, add saturated ammonia water and ultrasonically treat for 2h at an ultrasonic frequency of 10kHz, add tetraethyl orthosilicate and ultrasonically treat for 2h under stirring at an ultrasonic frequency of 10kHz, let stand for 6h, filter, wash with deionized water, vacuum dry, grind through a 100-mesh sieve; add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamide amine, stir at a temperature of 80°C for 2h at a stirring speed of 200r / min to obtain pretreated silicate; S2, mixing the pretreated silicate, loaded silica, organic bentonite, zinc oxide, N,N'-m-phenylene bismaleimide, and antioxidant 445, and stirring at a speed of 200 r / min for 20 min to obtain a mixture; S3, putting the nitrile rubber, styrene butadiene rubber and the mixed material into an internal mixer and mixing for 20 min, the mixing temperature is 90° C., the internal mixer speed is 150 r / min, a cross-linking agent is added thereto, and mixing is carried out at a temperature of 180° C. for 2 h to obtain a mixed material; S4. Cool the mixed material to 130°C, add stearic acid and sodium methylene dinaphthalene sulfonate in sequence, and plasticize for 30 minutes, then transfer the mixed material to an open mill to produce sheets.
[0034] Example 3: A rubber composite material for high-performance tires, the raw materials of which include: 70g of nitrile rubber, 25g of styrene-butadiene rubber, 12g of muscovite powder, 1.7g of saturated ammonia water, 7g of tetraethyl orthosilicate, 9g of amino-terminated liquid nitrile rubber, 2g of graphene oxide, 1.7g of 3.0-generation carboxyl-terminated polyamide amine, 7g of loaded silica, 4g of organic bentonite, 0.2g of zinc oxide, 2.5g of cross-linking agent, 1.2g of triallyl isocyanurate, 2.5g of antioxidant 4010, 1.5g of stearic acid, and 2.5g of triethylene glycol diisooctanoate.
[0035] The cross-linking agent is composed of sulfur and bis(tert-butylperoxyisopropyl)benzene in a mass ratio of 11:6.
[0036] The loaded silica was prepared by the following specific operation: 1.2 g of zirconium acetate and 1.8 g of yttrium acetate were added to 30 g of deionized water and stirred evenly, 4 g of urea was added thereto, stirred at 82°C for 9 h, centrifuged, washed, and vacuum dried, added to 30 g of 55% by mass ethanol aqueous solution, 1.5 g of saturated ammonia water was added thereto and stirred evenly, 2.5 g of tetraethyl orthosilicate was added thereto under stirring, stirred at 42°C for 12 h, centrifuged, washed, and vacuum dried.
[0037] The method for preparing the above-mentioned high-performance tire rubber composite material comprises the following steps: S1. Add muscovite powder to 70g of 55% ethanol aqueous solution and ultrasonically treat for 80min at an ultrasonic frequency of 12kHz. Add saturated ammonia water and ultrasonically treat for 80min at an ultrasonic frequency of 9kHz. Add tetraethyl orthosilicate and ultrasonically treat for 80min at an ultrasonic frequency of 9kHz under stirring. Let stand for 3h, filter, wash with deionized water, vacuum dry, and grind through a 100-mesh sieve; add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamide amine, stir at a temperature of 77°C for 80min at a stirring speed of 180r / min to obtain pretreated silicate; S2, mixing the pretreated silicate, loaded silica, organic bentonite, zinc oxide, triallyl isocyanurate, and antioxidant 4010, and stirring at a speed of 100 r / min for 18 min to obtain a mixture; S3, putting the nitrile rubber, styrene butadiene rubber and the mixed material into an internal mixer and mixing for 12 min, the mixing temperature is 85 ° C, the internal mixer speed is 80r / min, adding a cross-linking agent thereto, mixing at a temperature of 175 ° C for 80 min, to obtain a mixed material; S4. Cool the mixed material to 125°C, add stearic acid and triethylene glycol diisooctanoate in sequence, and plasticize for 15 minutes, then transfer the mixed material to an open mill to produce sheets.
[0038] Embodiment 4: A rubber composite material for high-performance tires, the raw materials of which include: 90g of nitrile rubber, 15g of styrene-butadiene rubber, 18g of muscovite powder, 1.3g of saturated ammonia water, 9g of tetraethyl orthosilicate, 7g of amino-terminated liquid nitrile rubber, 4g of graphene oxide, 1.3g of 3.0-generation carboxyl-terminated polyamide amine, 9g of loaded silica, 2g of organic bentonite, 0.8g of zinc oxide, 1.5g of cross-linking agent, 1.8g of N,N'-m-phenylene bismaleimide, 1.5g of antioxidant TMQ, 2.5g of stearic acid, and 1.5g of triethylene glycol diisooctanoate.
[0039] The cross-linking agent is composed of sulfur and dicumyl peroxide in a mass ratio of 7:2.
[0040] The loaded silica was prepared by the following specific operation: 1.8 g of zirconium acetate and 1.2 g of yttrium acetate were added to 40 g of deionized water and stirred evenly, 2 g of urea was added thereto, the mixture was stirred at 88°C for 7 h, centrifuged, washed, and vacuum dried, and then added to 40 g of 45% ethanol aqueous solution, 2.5 g of saturated ammonia water was added thereto and stirred evenly, 1.5 g of tetraethyl orthosilicate was added thereto under stirring, the mixture was stirred at 48°C for 8 h, centrifuged, washed, and vacuum dried.
[0041] The method for preparing the above-mentioned high-performance tire rubber composite material comprises the following steps: S1. Add muscovite powder to 90g of 45% ethanol aqueous solution and ultrasonically treat for 100min at an ultrasonic frequency of 6kHz. Add saturated ammonia water and ultrasonically treat for 100min at an ultrasonic frequency of 6kHz. Add tetraethyl orthosilicate and ultrasonically treat for 100min under stirring at an ultrasonic frequency of 6kHz. Let stand for 5h, filter, wash with deionized water, vacuum dry, and grind through a 100-mesh sieve. Add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamide amine, stir at 73°C for 100min at a stirring speed of 120r / min to obtain pretreated silicate. S2, mixing the pretreated silicate, loaded silica, organic bentonite, zinc oxide, N,N'-m-phenylene bismaleimide, and antioxidant TMQ, and stirring at a speed of 160 r / min for 12 min to obtain a mixture; S3, putting the nitrile rubber, styrene butadiene rubber and the mixed material into an internal mixer and mixing them for 18 min, the mixing temperature is 75 ° C, the internal mixer speed is 120r / min, adding a cross-linking agent thereto, mixing at a temperature of 165 ° C for 100 min, to obtain a mixed material; S4. Cool the mixed material to 115°C, add stearic acid and triethylene glycol diisooctanoate in sequence, and plasticize for 25 minutes, then transfer the mixed material to an open mill to produce sheets.
[0042] Example 5: A rubber composite material for high-performance tires, the raw materials of which include: 80g of nitrile rubber, 20g of styrene-butadiene rubber, 15g of muscovite powder, 1.5g of saturated ammonia water, 8g of tetraethyl orthosilicate, 8g of amino-terminated liquid nitrile rubber, 3g of graphene oxide, 1.5g of 3.0-generation carboxyl-terminated polyamide amine, 8g of loaded silica, 3g of organic bentonite, 0.5g of zinc oxide, 2g of cross-linking agent, 1.5g of triallyl isocyanurate, 2g of antioxidant DNP, 2g of stearic acid, and 2g of triethylene glycol diisooctanoate.
[0043] The cross-linking agent is composed of sulfur and bis(tert-butylperoxyisopropyl)benzene in a mass ratio of 5:2.
[0044] The loaded silica was prepared by the following specific operation: 1.5 g of zirconium acetate and 1.5 g of yttrium acetate were added to 35 g of deionized water and stirred evenly, 3 g of urea was added thereto, stirred at 85°C for 8 h, centrifuged, washed, and vacuum dried, added to 35 g of 50% by mass ethanol aqueous solution, 2 g of saturated ammonia water was added thereto and stirred evenly, 2 g of tetraethyl orthosilicate was added thereto under stirring, stirred at 45°C for 10 h, centrifuged, washed, and vacuum dried.
[0045] The method for preparing the above-mentioned high-performance tire rubber composite material comprises the following steps: S1. Add muscovite powder to 80g of 50% ethanol aqueous solution and ultrasonically treat for 90min at an ultrasonic frequency of 9kHz, add saturated ammonia water and ultrasonically treat for 90min at an ultrasonic frequency of 7.5kHz, add tetraethyl orthosilicate and ultrasonically treat for 90min at an ultrasonic frequency of 7.5kHz under stirring, let stand for 4h, filter, wash with deionized water, vacuum dry, and grind through a 100-mesh sieve; add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamide amine, stir at a temperature of 75°C for 90min at a stirring speed of 150r / min to obtain pretreated silicate; S2, mixing the pretreated silicate, loaded silica, organic bentonite, zinc oxide, triallyl isocyanurate, and antioxidant DNP, and stirring at a speed of 120 r / min for 15 min to obtain a mixture; S3, putting the nitrile rubber, styrene butadiene rubber and the mixed material into an internal mixer and mixing them for 15 min, the mixing temperature is 80° C., the internal mixer speed is 100 r / min, adding a crosslinking agent thereto, mixing at a temperature of 170° C. for 90 min, to obtain a mixed material; S4. Cool the mixed material to 120°C, add stearic acid and triethylene glycol diisooctanoate in sequence, and plasticize for 20 minutes, then transfer the mixed material to an open mill to produce sheets.
[0046] Comparative Example 1: A rubber composite material for high-performance tires, the raw materials of which include: 80g of nitrile rubber, 20g of styrene-butadiene rubber, 15g of muscovite powder, 1.5g of saturated ammonia water, 8g of tetraethyl orthosilicate, 8g of amino-terminated liquid nitrile rubber, 3g of graphene oxide, 1.5g of 3.0-generation carboxyl-terminated polyamide amine, 8g of loaded silica, 3g of organic bentonite, 0.5g of zinc oxide, 2g of cross-linking agent, 1.5g of triallyl isocyanurate, 2g of antioxidant DNP, 2g of stearic acid, and 2g of triethylene glycol diisooctanoate.
[0047] The cross-linking agent is composed of sulfur and bis(tert-butylperoxyisopropyl)benzene in a mass ratio of 5:2.
[0048] The loaded silica was prepared by the following specific operation: 1.5 g of zirconium acetate and 1.5 g of yttrium acetate were added to 35 g of deionized water and stirred evenly, 3 g of urea was added thereto, stirred at 85°C for 8 h, centrifuged, washed, and vacuum dried, added to 35 g of 50% by mass ethanol aqueous solution, 2 g of saturated ammonia water was added thereto and stirred evenly, 2 g of tetraethyl orthosilicate was added thereto under stirring, stirred at 45°C for 10 h, centrifuged, washed, and vacuum dried.
[0049] The method for preparing the above-mentioned high-performance tire rubber composite material comprises the following steps: S1. Add ethyl orthosilicate to 80g of 50% ethanol aqueous solution and ultrasonically treat for 90min at an ultrasonic frequency of 9kHz, add saturated ammonia water and ultrasonically treat for 90min at an ultrasonic frequency of 7.5kHz, let stand for 4h, filter, wash with deionized water, vacuum dry, add muscovite powder and mix evenly, grind through a 100-mesh sieve; add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamide amine, stir at a temperature of 75°C for 90min at a stirring speed of 150r / min to obtain pretreated silicate; S2, mixing the pretreated silicate, loaded silica, organic bentonite, zinc oxide, triallyl isocyanurate, and antioxidant DNP, and stirring at a speed of 120 r / min for 15 min to obtain a mixture; S3, putting the nitrile rubber, styrene butadiene rubber and the mixed material into an internal mixer and mixing them for 15 min, the mixing temperature is 80° C., the internal mixer speed is 100 r / min, adding a crosslinking agent thereto, mixing at a temperature of 170° C. for 90 min, to obtain a mixed material; S4. Cool the mixed material to 120°C, add stearic acid and triethylene glycol diisooctanoate in sequence, and plasticize for 20 minutes, then transfer the mixed material to an open mill to produce sheets.
[0050] Comparative Example 2: A rubber composite material for high-performance tires, the raw materials of which include: 80g of nitrile rubber, 20g of styrene-butadiene rubber, 15g of muscovite powder, 1.5g of saturated ammonia water, 8g of tetraethyl orthosilicate, 8g of amino-terminated liquid nitrile rubber, 3g of graphene oxide, 1.5g of 3.0-generation carboxyl-terminated polyamide amine, 8g of loaded silica, 3g of organic bentonite, 0.5g of zinc oxide, 2g of cross-linking agent, 1.5g of triallyl isocyanurate, 2g of antioxidant DNP, 2g of stearic acid, and 2g of triethylene glycol diisooctanoate.
[0051] The cross-linking agent is composed of sulfur and bis(tert-butylperoxyisopropyl)benzene in a mass ratio of 5:2.
[0052] The loaded silica was prepared by the following specific operation: 1.5 g of zirconium acetate and 1.5 g of lanthanum acetate were added to 35 g of deionized water and stirred evenly, 3 g of urea was added thereto, the mixture was stirred at 85°C for 8 h, centrifuged, washed, and vacuum dried, and then added to 35 g of 50% by mass ethanol aqueous solution, 2 g of saturated ammonia water was added thereto and stirred evenly, 2 g of tetraethyl orthosilicate was added thereto under stirring, the mixture was stirred at 45°C for 10 h, centrifuged, washed, and vacuum dried.
[0053] The method for preparing the above-mentioned high-performance tire rubber composite material comprises the following steps: S1. Add muscovite powder to 80g of 50% ethanol aqueous solution and ultrasonically treat for 90min at an ultrasonic frequency of 9kHz, add saturated ammonia water and ultrasonically treat for 90min at an ultrasonic frequency of 7.5kHz, add tetraethyl orthosilicate and ultrasonically treat for 90min at an ultrasonic frequency of 7.5kHz under stirring, let stand for 4h, filter, wash with deionized water, vacuum dry, and grind through a 100-mesh sieve; add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamide amine, stir at a temperature of 75°C for 90min at a stirring speed of 150r / min to obtain pretreated silicate; S2, mixing the pretreated silicate, loaded silica, organic bentonite, zinc oxide, triallyl isocyanurate, and antioxidant DNP, and stirring at a speed of 120 r / min for 15 min to obtain a mixture; S3, putting the nitrile rubber, styrene butadiene rubber and the mixed material into an internal mixer and mixing them for 15 min, the mixing temperature is 80° C., the internal mixer speed is 100 r / min, adding a crosslinking agent thereto, mixing at a temperature of 170° C. for 90 min, to obtain a mixed material; S4. Cool the mixed material to 120°C, add stearic acid and triethylene glycol diisooctanoate in sequence, and plasticize for 20 minutes, then transfer the mixed material to an open mill to produce sheets.
[0054] Comparative Example 3: A rubber composite material for high-performance tires, the raw materials of which include: 80g of nitrile rubber, 20g of styrene-butadiene rubber, 15g of muscovite powder, 1.5g of saturated ammonia water, 8g of tetraethyl orthosilicate, 8g of amino-terminated liquid nitrile rubber, 3g of graphene oxide, 1.5g of 3.0-generation carboxyl-terminated polyamide amine, 8g of loaded silica, 3g of organic bentonite, 0.5g of zinc oxide, 2g of cross-linking agent, 1.5g of triallyl isocyanurate, 2g of antioxidant DNP, 2g of stearic acid, and 2g of triethylene glycol diisooctanoate.
[0055] The cross-linking agent is composed of sulfur and bis(tert-butylperoxyisopropyl)benzene in a mass ratio of 5:2.
[0056] The loaded silica was prepared by the following specific operation: 1.5 g of zirconium acetate and 1.5 g of yttrium acetate were added to 35 g of deionized water and stirred evenly, 3 g of urea was added thereto, stirred at 85°C for 8 h, centrifuged, washed, and vacuum dried, added to 35 g of 50% by mass ethanol aqueous solution, 2 g of saturated ammonia water was added thereto and stirred evenly, 2 g of tetraethyl orthosilicate was added thereto under stirring, stirred at 45°C for 10 h, centrifuged, washed, and vacuum dried.
[0057] The method for preparing the above-mentioned high-performance tire rubber composite material comprises the following steps: S1. Add muscovite powder to 80g of 50% ethanol aqueous solution and ultrasonically treat for 90min at an ultrasonic frequency of 9kHz. Add saturated ammonia water and ultrasonically treat for 90min at an ultrasonic frequency of 7.5kHz. Add tetraethyl orthosilicate and ultrasonically treat for 90min at an ultrasonic frequency of 7.5kHz under stirring. Let stand for 4h, filter, wash with deionized water, vacuum dry, and grind through a 100-mesh sieve; add amino-terminated liquid nitrile rubber and carboxyl-terminated polyamide amine, stir at a temperature of 75°C for 90min at a stirring speed of 150r / min to obtain pretreated silicate; S2, mixing the pretreated silicate, loaded silica, organic bentonite, graphene oxide, zinc oxide, triallyl isocyanurate, and antioxidant DNP, and stirring at a speed of 120 r / min for 15 min to obtain a mixture; S3, putting the nitrile rubber, styrene butadiene rubber and the mixed material into an internal mixer and mixing them for 15 min, the mixing temperature is 80° C., the internal mixer speed is 100 r / min, adding a crosslinking agent thereto, mixing at a temperature of 170° C. for 90 min, to obtain a mixed material; S4. Cool the mixed material to 120°C, add stearic acid and triethylene glycol diisooctanoate in sequence, and plasticize for 20 minutes, then transfer the mixed material to an open mill to produce sheets.
[0058] The composite materials obtained in Example 5 and Comparative Examples 1-3 were subjected to performance tests, as follows: (1) With reference to GB / T 528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”, the tensile strength, 100% modulus and elongation at break of each group of specimens were measured at a tensile speed of 500±5mm / min. (2) The tear strength of each group of specimens was measured with reference to GB / T 529-2008 “Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-shaped, right-angled and crescent-shaped specimens)”. Each specimen was a right-angled specimen.
[0059] like Figure 1 and Figure 2 As shown, the tensile strength, 100% tensile strength, elongation at break and tear strength of the composite material obtained in Example 5 are all the highest, which are better than those of Comparative Examples 1-3 (P < 0.05).
[0060] The composite materials obtained in Example 5 and Comparative Examples 1-3 were subjected to dry friction and wear tests, and the test conditions were as follows: (1) the load was 60 N and the sliding speed was 70 mm / s, (2) the load was 140 N and the sliding speed was 300 mm / s; the friction coefficient and wear rate of each group of samples were measured.
[0061] like Figure 3 and Figure 4 As shown, when the groups of samples are compared longitudinally, as the load increases, the sliding speed becomes faster, resulting in a decrease in the friction coefficient and wear rate of each group of samples; however, when the groups of samples are compared horizontally, the friction coefficient and wear rate of the composite material obtained in Example 5 are always the lowest, which is better than that of Comparative Examples 1-3 (P < 0.05).
[0062] The applicant believes that this is because the present invention loads nano silicon dioxide on layered silicate minerals, not only nano silicon dioxide is not easy to fall off, but also has excellent dispersibility with amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamide amine, and has high mutual bonding strength. Compared with directly adding layered silicate minerals, the product has excellent tear resistance and excellent tensile stress at a lower deformation (100%). At the same time, the present invention uses zirconium acetate and yttrium acetate to load nano silicon dioxide on its surface, and compound it with pretreated silicate, which has excellent reinforcement effect under the premise of avoiding the addition of carbon black, and can improve the interface between silicon dioxide and rubber, thereby promoting good dispersion of silicon dioxide in rubber, and forming multiple cross-linking sites between nitrile rubber and styrene-butadiene rubber molecular segments, giving the product excellent wear resistance and tear resistance, and better durability than ordinary tires.
[0063] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A rubber composite material for high-performance tires, characterized in that: The raw materials include, by mass, 50-100 parts of nitrile rubber, 10-30 parts of styrene-butadiene rubber, 10-20 parts of silicate mineral powder, 1-2 parts of saturated ammonia water, 5-10 parts of tetraethyl orthosilicate, 5-10 parts of amino-terminated liquid nitrile rubber, 1-5 parts of graphene oxide, 1-2 parts of carboxyl-terminated polyamide amine, 5-10 parts of loaded silicon dioxide, 1-5 parts of organic bentonite, 0.1-1 parts of zinc oxide, 1-3 parts of crosslinking agent, 1-2 parts of vulcanization accelerator, 1-3 parts of antioxidant, 1-3 parts of stearic acid and 1-3 parts of dispersant.
2. The high performance tire rubber composite material according to claim 1, characterized in that: The silicate mineral powder is at least one of talc powder, muscovite powder and montmorillonite powder.
3. The high performance tire rubber composite material according to claim 1, characterized in that: The cross-linking agent includes sulfur and organic peroxide, and the mass ratio of sulfur to organic peroxide is 2-3:0.5-1.5; The organic peroxide is diisopropylbenzene peroxide or / and bis(tert-butylperoxyisopropyl)benzene.
4. The high performance tire rubber composite material according to claim 1, characterized in that: The vulcanization accelerator is triallyl isocyanurate or / and N,N'-m-phenylene bismaleimide.
5. The high performance tire rubber composite material according to claim 1, characterized in that: The dispersant is sodium methylene dinaphthalene sulfonate or triethylene glycol diisooctanoate.
6. The high performance tire rubber composite material according to claim 1, characterized in that: The antioxidant is at least one of antioxidant BLE, antioxidant 445, antioxidant 4010, antioxidant DNP, and antioxidant TMQ.
7. The high performance tire rubber composite material according to claim 1, characterized in that: The loaded silica is prepared by the following specific operation: zirconium acetate and yttrium acetate are added to water and stirred evenly, urea is added thereto, stirred at 80-90°C for 5-10 hours, centrifuged, washed, vacuum dried, added to ethanol aqueous solution, saturated ammonia water is added thereto and stirred evenly, tetraethyl orthosilicate is added thereto under stirring, stirred at 40-50°C for 5-15 hours, centrifuged, washed, and vacuum dried.
8. The high performance tire rubber composite material according to claim 7, characterized in that: The mass ratio of zirconium acetate, yttrium acetate, saturated ammonia water and tetraethyl orthosilicate is 1-2:1-2:1-3:1-3.
9. A method for preparing the rubber composite material for high-performance tires according to any one of claims 1 to 8, characterized in that: The steps include: S1. Add silicate mineral powder to ethanol aqueous solution and ultrasonically treat for 1-2h, add saturated ammonia water and ultrasonically treat for 1-2h, add ethyl orthosilicate and ultrasonically treat for 1-2h under stirring, let stand for 2-6h, filter, wash, vacuum dry, grind and sieve; add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamide amine, stir at 70-80°C for 1-2h to obtain pretreated silicate; S2, mixing the pretreated silicate, loaded silica, organic bentonite, zinc oxide, vulcanization accelerator, and antioxidant to obtain a mixture; S3, mixing the nitrile rubber, styrene butadiene rubber and the mixed material for 10-20 minutes at a mixing temperature of 70-90° C., adding a crosslinking agent thereto, and mixing at 160-180° C. for 1-2 hours to obtain a mixed material; S4. Cool the mixed material to 110-130°C, add stearic acid and dispersant in sequence, and plasticize for 10-30 minutes to form sheets.
10. The method for preparing the rubber composite material for high-performance tires according to claim 9, characterized in that: In S1, the frequency of ultrasonic treatment after the silicate mineral powder is added to the ethanol aqueous solution is 5-15 kHz, the frequency of ultrasonic treatment after adding saturated ammonia water is 5-10 kHz, and the frequency of ultrasonic treatment after adding tetraethyl orthosilicate is 5-10 kHz.
Citation Information
Patent Citations
ZrO2-SiO2 compound oxides, its preparation method and application
CN101007268A
Novel method for crosslinking acrylonitrile butadiene by supported transient metal
CN101486800A
Abrasion resistant rubber and preparation method thereof
CN105400017A
Elastic high temperature resistant ceramic heat insulation tile and preparation method of same
CN109020593A
Silica NANO particle, method for producing the same, complex and method for producing the same
KR1020130024993A